2010
DOI: 10.1126/science.1181928
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Amplify Inflammation in Arthritis via Collagen-Dependent Microparticle Production

Abstract: In addition to their pivotal role in thrombosis and wound repair, platelets participate in inflammatory responses. We investigated the role of platelets in the autoimmune disease rheumatoid arthritis. We identified platelet microparticles—submicrometer vesicles elaborated by activated platelets—in joint fluid from patients with rheumatoid arthritis and other forms of inflammatory arthritis, but not in joint fluid from patients with osteoarthritis. Platelet microparticles were proinflammatory, eliciting cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
962
6
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 964 publications
(1,029 citation statements)
references
References 28 publications
26
962
6
17
Order By: Relevance
“…Gerrard et al39 observed similarly altered ultrastructure of A23187‐stimulated platelets in suspension by electron microscopy, and reported that platelets exposed to high A23187 concentrations lost their alpha and dense granules, and often had the cytoplasmic gel concentrated in a dense mass, with swollen membranes that were pulled away from the cell contents. We observed extracellular vesicles (EVs) in T+C‐ or A23187‐stimulated conditions; in some cases, these EVs appeared to be associated with or blebbing from the platelet surface, similar to the EVs budding from platelets incubated in the presence of fibroblast‐like synoviocytes observed by Boilard et al40 and from platelets activated with thrombin observed by Ponomareva et al,41 suggesting that the free EVs had been released from the balloon platelets.…”
Section: Discussionsupporting
confidence: 74%
“…Gerrard et al39 observed similarly altered ultrastructure of A23187‐stimulated platelets in suspension by electron microscopy, and reported that platelets exposed to high A23187 concentrations lost their alpha and dense granules, and often had the cytoplasmic gel concentrated in a dense mass, with swollen membranes that were pulled away from the cell contents. We observed extracellular vesicles (EVs) in T+C‐ or A23187‐stimulated conditions; in some cases, these EVs appeared to be associated with or blebbing from the platelet surface, similar to the EVs budding from platelets incubated in the presence of fibroblast‐like synoviocytes observed by Boilard et al40 and from platelets activated with thrombin observed by Ponomareva et al,41 suggesting that the free EVs had been released from the balloon platelets.…”
Section: Discussionsupporting
confidence: 74%
“…The flow cytometry instrument settings and MP gating were adopted from previous works [2,12,16]. We used Megamix beads (BioCytex, Marseille, France) to determine the gate for MPs, as described previously [2,18].…”
Section: Flow Cytometric Analysis Of Pfp Samplesmentioning
confidence: 99%
“…However, there are remaining debated questions including the use of anticoagulants for MP analysis. Although most studies used sodium-citrate tubes, some groups applied ACD (acid-citrate-dextrose) tubes in their studies [14][15][16]. A recent report by Jayachandran et al suggested that neither citrate nor ACD tubes were suitable for MP measurement as these anticoagulants may eliminate MPs from plasma [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, elevated levels of CD3+ and CD8+ T cell-derived and platelet-derived EVs are detected in RA SF [2,3]. Furthermore, SF EVs are described as having potent pro-inflammatory properties that might contribute to the perpetuation of joint inflammation in RA [1,35]. Understanding the composition and function of SF EVs is therefore of great interest and may provide insight into pathogenesis of joint diseases.…”
Section: Introductionmentioning
confidence: 99%